Efektifitas dan Keamanan Terapi Sodium Glucose Co-transporter 2 (SGLT2) Inhibitor pada Gagal Jantung: Narrative Literatur Review - Diniah, Melisa Nur; Suharjono, Suharjono (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2025)
Heart Failure (HF) is a clinical syndrome due to structural or functional defects in the myocardium causing impaired ventricular filling or ejection of blood. HF is currently divided into 3 types namely HFrEF, HFpEF, and HFmEF. In the last 5 years, treatment in HF patients has been updated to be able to use SGLT 2 inhibitor therapy. Initially, SGLT2 inhibitors were a therapy given to patients with type 2 diabetes mellitus. This recommendation was given because SGLT2 inhibitors can reduce the risk of cardiovascular death and reduce the incidence of repeated hospitalizations in HF patients. The safety of SGLT2 inhibitor administration is also reported to not cause serious side effects.